Role of IRE1α/XBP1/CHOP/NLRP3 Signalling Pathway in Neonicotinoid Imidacloprid-Induced Pancreatic Dysfunction in Rats and Antagonism of Lycopene: In Vivo and Molecular Docking Simulation Approaches - Walaa Bayoumie El Gazzar; Heba Bayoumi; Heba S. Youssef; Tayseer A. Ibrahim; Reham M. Abdelfatah; Noha M. Gamil; Mervat K. Iskandar; Amal M. Abdel-Kareim; Shaymaa M. Abdelrahman; Mohammed A. Gebba; Mona Atya Mohamed; Maha M. Mokhtar; et al. (Toxics, 2024)
Imidacloprid (IMI) is a commonly used new-generation pesticide that has numerous harmful effects on non-targeted organisms, including animals. This study analysed both the adverse effects on the pancreas following oral consumption of imidacloprid neonicotinoids (45 mg/kg daily for 30 days) and the potential protective effects of lycopene (LYC) administration (10 mg/kg/day for 30 days) with IMI exposure in male Sprague–Dawley rats. The apoptotic, pyroptotic, inflammatory, oxidative stress, and endoplasmic reticulum stress biomarkers were evaluated, along with the histopathological alterations. Upon IMI administration, noticeable changes were observed in pancreatic histopathology. Additionally, elevated oxidative/endoplasmic reticulum-associated stress biomarkers, inflammatory, pyroptotic, and apoptotic biomarkers were also observed following IMI administration. LYC effectively reversed these alterations by reducing oxidative stress markers (e.g., MDA) and enhancing antioxidant enzymes (SOD, CAT). It downregulated ER stress markers (IRE1α, XBP1, CHOP), decreased pro-inflammatory cytokines (TNF-α, IL-1β), and suppressed pyroptotic (NLRP3, caspase-1) along with apoptotic markers (Bax, cleaved caspase-3). It also improved the histopathological and ultrastructure alterations brought on by IMI toxicity.